Alteración dentofacial de una paciente clase III y su manejo ortodóncico quirúrgico: reporte de caso clínico - Pedro María Jaramillo-V.; Francisco Levi Duque-S. (Revista Facultad de Odontología Universidad de Antioquia, 2005)
A clinical case report of a fifteen-year-old female with an Angle class III malocclusion and with maxillary deficiency and mandibular prognathism is presented. The patient initially consulted at an early age and a decision was made to delay comprehensive treatment until her skeletal growth ended. Alexander’s prescription (Ormco) was used for orthodontic treatment and a mandibular surgical set back only with oblique ramous osteotomy was performed achieving an adequate occlusal relationship and facial balance. This patient was treated according to the protocol established for the orthodontic and oral and maxillofacial surgery postgraduate programs of the Dental Faculty of the University of Antioquia.